2021
DOI: 10.3389/fmed.2021.744713
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Modest Alcohol Consumption on Non-alcoholic Fatty Liver Disease: A Systematic Review and Meta-Analysis

Abstract: Background and Objective: There is no consensus regarding modest alcohol consumption in patients with non-alcoholic fatty liver disease (NAFLD) due to conflicting results. The aim of this meta-analysis was to examine the effects of modest alcohol consumption on histological severity, histological course, hepatocellular carcinoma, and long-term clinical outcomes in NAFLD patients.Methods: We searched MEDLINE and EMBASE databases from inception to October 2020 for studies evaluating the effects of modest alcohol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 49 publications
(107 reference statements)
1
20
0
Order By: Relevance
“…A threeyear longitudinal study with 4 waves' repeated measurements including up to 3773 Japanese adults found that light to moderate alcohol consumption was associated with a reduced risk of NAFLD in both sexes [30]. This inverse association was also identified in a recent meta-analysis of 14 observational studies [31]. However, moderate alcohol use compared to nondrinking was associated with less improvement in steatosis and level of aspartate transaminase in 285 NAFLD patients after a mean follow-up period of 47 months [9].…”
Section: Discussionmentioning
confidence: 71%
“…A threeyear longitudinal study with 4 waves' repeated measurements including up to 3773 Japanese adults found that light to moderate alcohol consumption was associated with a reduced risk of NAFLD in both sexes [30]. This inverse association was also identified in a recent meta-analysis of 14 observational studies [31]. However, moderate alcohol use compared to nondrinking was associated with less improvement in steatosis and level of aspartate transaminase in 285 NAFLD patients after a mean follow-up period of 47 months [9].…”
Section: Discussionmentioning
confidence: 71%
“…They found that moderate alcohol intake was associated with a pooled HR of 3.77 for developing HCC (Figure 4). 94 Kimura et al also showed that moderate drinking appeared to be a risk factor for HCC in patients with NAFLD, particularly those with advanced fibrosis. 100 A prospective study in a general population cohort based in the US showed that modest alcohol consumption was associated with a significant reduction in all-cause mortality.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 97%
“…93 A more recent meta-analysis also suggested that moderate alcohol consumption was associated with reduced odds of developing NASH and advanced fibrosis. 94 However, most of these studies employed observational cross-sectional designs.…”
Section: The Intricate Relationship Between Alcohol Consumption and N...mentioning
confidence: 99%
“…Although alcohol is a carcinogen with a well-known dose-risk relationship, 32,33 meta-analyses based on many previous studies have published results that moderate alcohol consumption showed a protective effect against NAFLD (Table 2). [26][27][28]34 Interestingly, Sookoian et al suggest that moderate alcohol consumption is associated with a significant protective effect against NAFLD (Table 2). Body mass index (BMI) was not a statistically significant confounding factor in meta-regression analysis (slope=0.01, p<0.44) but moderate alcohol consumption was more protective in women than men (53% in women, 30% in men).…”
Section: [Moderate Alcohol Drinking: Beneficial or Detrimental?]mentioning
confidence: 99%
“…45 A meta-analysis by Wongtrakul et al, narrowed down the analysis target to NAFLD patients with moderate alcohol consumption only, suggested significant HR (3.77, 95% CI, 1.75-8.15; I 2 =0%) for developing HCC. 34 There are pitfalls to consider before accepting the conflicting research results discussed above.…”
Section: [Moderate Alcohol Drinking: Beneficial or Detrimental?]mentioning
confidence: 99%